Maternal and Child Health Handbook Utilization, Quantity and Quality of Antenatal Services, and Maternal Emergency Rates in Padang City in 2022 - Ningsih, Rena Afri; Yusrawati, Yusrawati; Serudji, Joserizal (UI Scholars Hub, 2023)
This study analyzed the relationship between the utilization of the Indonesian Ministry of Health’s Maternal and Child Health Handbook and the quantity and quality of antenatal care to maternal emergency levels. This study applied mixed methods with a consecutive sampling technique and included 108 mothers undergoing maternal emergencies at a central general hospital (quantitative) and eight mothers, seven midwives, and five cadres at primary health cares (qualitative) as informants. The result showed a relationship between the utilization of the Maternal and Child Health Care Handbook (p-value = 0.043), the quantity of antenatal care (p-value